DESCRIPTION OF WORKERS' KNOWLEDGE AND ATTITUDES TOWARDS FIRE HAZARDS IN THE CHEMICAL MANUFACTURING INDUSTRY IN 2021 - Rizkhe Safina; Suryono, Hadi; Ngadino; Winarko (Jurnal Higiene Sanitasi, 2021)
The level of knowledge and attitudes could affect workers in dealing with fire hazards. The purpose of this study was to describe the knowledge and attitudes of workers towards fire hazards (based on age, education, length of service, and fire simulation) at the chemical manufacturing industry.Type of research was descriptive. The sampling technique used was simple random sampling. The data that had been obtained was then analyzed descriptively by describing the data that had been collected. The results of the analysis were categorized and then described in the form of a narrative.From the results of the study indicate that the level of knowledge of respondents with a good category with a percentage of 95, 4% and respondents with a sufficient category with a percentage of 4, 6%. The attitude of the respondents in the category of strongly agreed with the percentage of 55%, the attitude of the respondents with the category of agreeing with the percentage of 43.1%, and the attitude of the respondents in the category of disagreeing with the percentage of 1.8%. the level pf knowledge and attitude of workers in the chemical manufacturing industry was influenced by age, education, length of work, and fire simulation. The advice given is that the company paid more attention to workers who have never participated in a fire simulation and installed posters to increase worker awareness in responding to fire hazards.